Interfacial bond behavior of FRP fabrics bonded to fiber-reinforced geopolymer mortar. (15th December 2015) - Khalid, Hammad R.; Ha, S.K.; Park, S.M.; Kim, G.M.; Lee, H.K.
Abstract: This paper presents the experimental investigation of composite-mortar three-point bending beam test setup, used to characterize the bond behavior between concrete/mortar and fiber-reinforced polymers (FRPs). With this aim, a series of experimental studies have been conducted by considering different FRP fabric types (carbon/glass and carbon/aramid), epoxy adhesives (E-1 and E-2), and notch depths (50 and 33 mm). In addition, a fiber-reinforced mortar, with different fiber contents (0, 0.5, 1 and 1.5 wt.%) was also used to investigate the effects of short fibers on the interface behavior. From the load–displacement curves in three-point bending beam tests, peak load ( Ppeak ), ultimate mid-span deflection ( δult ), and interfacial fracture energy ( GF, int ) of different bonded interfaces were evaluated. It is concluded from this study that this test setup is useful for the comparison of different bonded interfaces as true interfacial failure was observed, but the interfacial fracture energy ( GF, int ) obtained from these tests showed sensitivity to the notch depth. The incorporation of short steel fibers into mortar was not effective to improve the interfacial bond strength as not much fiber action was observed (near the bond line) during testing.